1986
DOI: 10.1007/bf00982668
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical localization of epidermal growth factor in rat and man

Abstract: Epidermal growth factor (EGF) is a peptide which stimulates cell mitotic activity and differentiation, has a cytoprotective effect on the gastroduodenal mucosa, and inhibits gastric acid secretion. The immunohistochemical localization of EGF in the Brunner's glands and the submandibular glands is well documented. The localization of EGF in other tissues is still unclarified. In the present study, the immunohistochemical localization of EGF in tissues from rat, man and a 20 week human fetus were investigated. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
91
0

Year Published

1988
1988
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 208 publications
(95 citation statements)
references
References 21 publications
3
91
0
Order By: Relevance
“…However, it has been demonstrated that Paneth cells produce and secrete antibacterial agents (lysozyme, cryptidin, and immunoglobulin A), hydrolases, lipases, and growth factors and modulators (Desai et al 1991;Quellette and Lualdi 1990;Saito et al 1988;Lechene de la Porte et al 1986;Poulsen et al 1986;Senegas-Balas et al 1984;Erlandsen et al 1974 Erlandsen et al , 1976Erlandsen and Parsons, 1973). The granules also contain a zinc-binding protein (Sawada et al 1994).…”
mentioning
confidence: 99%
“…However, it has been demonstrated that Paneth cells produce and secrete antibacterial agents (lysozyme, cryptidin, and immunoglobulin A), hydrolases, lipases, and growth factors and modulators (Desai et al 1991;Quellette and Lualdi 1990;Saito et al 1988;Lechene de la Porte et al 1986;Poulsen et al 1986;Senegas-Balas et al 1984;Erlandsen et al 1974 Erlandsen et al , 1976Erlandsen and Parsons, 1973). The granules also contain a zinc-binding protein (Sawada et al 1994).…”
mentioning
confidence: 99%
“…Our investigation showed that, following injection of 1251-EGF into the tail vein, radioactivity appeared not only in the submandibular gland, but also in the sublingual gland. In human salivary glands, the submandibular gland has a lower concentration of EGF (72), and only the serous (41,72) or duct cells (30) contain immunoreactive EGF. The control experiment with an excessive amount of unlabeled EGF showed that most of the EGF was not bound specifically to both salivary glands, a finding which indicates that endogenous EGF is taken up by the salivary glands.…”
Section: Salivary Glandmentioning
confidence: 99%
“…mEGF is localized in the granular convoluted tubule cells of the mouse submandibular glands (4,21,35) and other tissues and organs contain also EGF, e. g., central nervous system (16), kidney (43), prostate gland of the guinea pig (46) and various rat organs (41). It has been reported that hEGF was noted in submandibular gland duct and Brunner's gland (14) in anterior pituitary cells, gastric and pyloric glands, eccrine sweat glands, pancreatic islet cells, lactating breast gland, renal medulla, prostate gland, and ovary (27) and in Paneth cells in jejunum and serous cells of nasal glands (41). All those investigations utilized polyclonal anti-hEGF antiserum generated by highly purified hEGF isolated from human urine.…”
Section: Respiratory Systemmentioning
confidence: 99%
“…Urogastrone and human EGF (hEGF) are biologically equivalent; that is, they are probably the same polypeptide and chemically identical (19). Physiological and biological properties of hEGF in normal and diseased tissues of humans have been increasingly developed (27,41,49), however, the immunohistochemical expression of hEGF in various tissues and organs have not been well established. Previous papers have noted that serum or other body fluids and tissue extracts contain varying amounts of hEGF (24,32).…”
mentioning
confidence: 99%